Field notes and Ann Johnson letter to the editor, fall 1991 - Johnson, Annet al (1991)
List of birds and locations contributed by Ann Johnson with observers Robert I. Cecil, John Cecil and Jim Sinclair. Included with the field report is a letter from Ann Johnson to the editor that summarizes her fall bird observations. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed